Implementation of E-Module Buffer Solution To Improve Students' Critical Thinking Skills - Widyawati, Fitria (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to describe student activities, analyze improvement in students 'critical thinking skills, and analyze students' responses to learning using the buffer e-module solution. The method used was a one group pretest posttest with research subjects in class XI IPA 3 SMA Jaya Suti Abadi. The percentage of student activities in implementing this e-module is 93% with a very good category. Students' critical thinking skills have improved with an average value of n-gain of 0.59 in the medium category. The response of students who answered agreed to achieve 54% results, which means students like to learn with e-modules and e-modules get positive responses. The results of this study indicate that learning by applying a buffer solution e-module can be used as an alternative to improving students' critical thinking skills.